Attitudes and Knowledge With Covid-19 Prevention Behavior in Pabelan Village - Imamah, Ida Nur; Husain, Fida’; RBU, Dyah Rahmawatie (STIKES Adi Husada, 2023)
Socialization and direction on Covid-19 prevention have been disseminated throughout the population. There are still many people who have not behaved to do what is directed by the government. This happens due to the low literacy ability of the community and there are still many people who do not have access to information media, so the attitudes and knowledge possessed by the community are still minimal in the outbreak of this Covid-19 outbreak. Knowledge and attitudes are very important in determining one's behavior because knowledge forms beliefs that will then become the basis for a person in taking a stand and determining behavior toward certain objects. This study aims to determine the relationship between knowledge and attitudes toward Covid-19 prevention behavior in Pabelan Village. This research is analytical research with a cross-sectional design. The research was conducted on residents of Pabelan Kartasuro Sukoharjo Village with a total sample of 51 respondents. The sampling technique uses the simple random sample method. The Chi-Square test conducted obtained a p-value of > 0.05 (1.00) for the relationship between attitude and Covid-19 prevention behavior. The results of the analysis of the relationship of knowledge with Covid prevention behavior p>0,05. There is no relationship between attitudes and knowledge and Covid prevention behavior. Good attitudes and knowledge related to Covid are expected to be able to provide positive prevention behavior.